Tax reform: scope and limitations - Vallejo Zamudio, Luis E. (Universidad Pedagógica y Tecnológica de Colombia, 2015)
In the last days of 2014, the President passed the new tax reform (Law 1739 of 2014) thatgoes into effect since January 2015, which, according to Santos, “it does not affect neitherthe middle class of the country nor the small and medium companies”. The President alsostressed that the new tax revenues “are used for social and productive investment”.